Cerebral and carotid haemodynamic changes following cervical spinal cord stimulation. An experimental study. (1989)
Since it is accepted that spinal cord stimulation may produce segmentary vasodilation, it is presumable that when applied in the high cervical segments some carotid and cerebral blood flow changes can be expected. Following this assumption, 25 dogs and 25 goats were used. Under routine experimental conditions a C 7 laminectomy was performed in these animals and a bipolar lead introduced and manipulated in the epidural space till the right C 2 segment. Right common and internal carotid arteries of the dogs were isolated and electromagnetics probes placed for continuous monitoring of blood flow changes. Right internal maxillary artery was isolated and its branches ligated for flowmetry of hemispheric blood flow in the goat. 131 1 antipyrine also studied to control regional cerebral blood flow changes. Arterial pressure and blood gasometry were periodically determined to avoid masking results. Pulse width of 0.1 to 0.2 msec, 80 to 120 cps and amplitude to muscle contraction threshold at low rate were used as electrical parameters. After stimulation common and internal carotid blood flow increased with a mean of 60% and hemispheric blood flow with a mean of 55% according to flowmetry findings. 10doantipyrine studies showed an average increase of 35%. These changes were not modified by atropine, morphine and naloxone and partially blocked by indomethacin, cimetidine and propanolo!.